La resistencia y la fe mueven los cuerpos, la historia de Carlos Alberto Estacio, la vida de un bailarín de salsa en la ciudad de Cali (2023)
This document collects the parallel tales about the life story of Carlos Alberto Estacio as a product of a qualitative approach research using a descriptive/explanatory methodology. Therefore, the information presented below was collected through interviews, and documents supported by photos, newspaper clippings, magazines, and certifications. The recollection of information depended on actors like family members, dance colleagues, priests, nuns, teachers, and Carlos` students.